Climate Change and New Markets: Multi-Factorial Drivers of Recent Land-Use Change in The Semi-Arid Trans-Himalaya, Nepal - Meier, Wolfgang; Pohle, Perdita; Grießinger, Jussi (Land, 2022)
The Nepalese Mustang District is subject to profound environmental change. In recent decades, rising temperatures have been apparent, accompanied by increasing precipitation variability and a reduction in glacier extent. In a semi-arid climate, this reduces water availability and threatens irrigation-based subsidence agriculture. In addition, the region is experiencing rapid socio-economic change due to a new road connecting the former periphery to new markets downstream. This enables a higher market orientation for agricultural products and improved accessibility for tourists. In recent decades, these changes have triggered severe transformations in the local land-use systems and settlements, which are investigated in this study. Detailed on-site re-mappings of the settlements of Marpha and Kagbeni were performed based on historical maps from the early 1990s. Additionally, land-use patterns and functionality of buildings in the district capital of Jomsom and in the settlement Ranipauwa/Muktinath were mapped. For all settlements, a profound increase in cash crop (apple) cultivation can be observed since the 1990s. Recently, new cultivation practices such as intercropping have been extensively introduced as an adaptation strategy to climate extremes. Demand for different crops from the new markets downstream is causing a significant decline in local, well-established cultivation of traditional crops such as buckwheat. This corroborates with an increasing demand for freshwater for the enhanced vegetable cultivation used for inter-cropping. Simultaneously, the freshwater demands from the tourism sector are steadily increasing. In a region where water quality is deteriorating and springs are already drying up due to climate change, this will probably lead to further challenges regarding the allocation of water in the future.
CRIS-Team WoS Importer:2022-10-07